Optical laminate

KR1020260133716APending Publication Date: 2026-09-04SUMITOMO CHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
KR1020260021545
Authority / Receiving Office
KR · KR
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-02-28
Filing Date
2026-02-03
Publication Date
2026-09-04

Smart Images

  • Figure P1020260021545_ABST
    Figure P1020260021545_ABST
Patent Text Reader

Abstract

[Project] To provide an optical laminate capable of suppressing yellowing of PVA-based polarizers in high-temperature environments. [Solution] An optical laminate comprises a surface protection film, a first protection layer, a PVA-based polarizer, a second protection layer, an adhesive layer α, and a separator film in this order. At least one of the surface protection film and the separator film has a moisture-impermeable layer and a moisture-absorbing layer positioned closer to the PVA-based polarizer than to the moisture-impermeable layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to an optical laminate. Background Technology

[0002] Conventionally, in a polarizing plate having a PVA-based polarizer and a pair of protective layers placed therebetween, it is known that a moisture-proof layer is provided to increase high temperature resistance. Prior art literature

[0003] Patent Document 1: Japanese Patent Publication No. Hei 03-148603 The problem to be solved

[0004] In some applications, a component such as an image display panel is attached to one side of a polarizer containing a PVA-based polarizer, and a component such as a front panel or touch panel is attached to the other side. Since components such as image display panels and front panels / touch panels have low moisture permeability, if the polarizer is sandwiched between these components while the PVA-based polarizer contains a large amount of water, it becomes difficult to remove moisture from the PVA-based polarizer thereafter. Furthermore, if the polarizer is exposed to a high-temperature environment in this laminated state, the PVA-based polarizer is prone to yellowing due to moisture.

[0005] Therefore, conventionally, after attaching a component such as an image display panel to one side of the polarizing plate, and before attaching a component such as a front panel or touch panel to the other side of the polarizing plate, the polarizing plate was heat-treated in advance to remove moisture from the optical laminate.

[0006] The present invention has been made in consideration of the above problem, and aims to provide an optical laminate capable of suppressing yellowing of a PVA-based polarizer in an image display device in a high-temperature environment, even if a member such as an image display cell is attached to one side of a polarizer and a member such as a front plate / touch panel is attached to the other side of the polarizer without performing prior heat treatment of the polarizer. means of solving the problem

[0007] [1] An optical laminate comprising a surface protection film, a first protection layer, a PVA-based polarizer, a second protection layer, an adhesive layer α, and a separator film in this order,

[0008] An optical laminate having at least one of the surface protection film and the separator film, the impermeable layer, and a moisture-absorbing layer positioned closer to the PVA-based polarizer than the impermeable layer.

[0009] [2] The surface protection film has the above moisture-impermeable layer and the above moisture-absorbing layer,

[0010] An optical laminate described in [1], wherein the second protective layer is a moisture-impermeable layer.

[0011] [3] The above surface protection film has an impermeable layer and a moisture-absorbing layer,

[0012] The optical laminate described in [1] or [2], wherein the above separating film has a moisture-impermeable layer.

[0013] [4] An optical laminate described in [3], wherein the separating film further comprises a moisture-absorbing layer positioned closer to the PVA-based polarizer than to the moisture-impermeable layer.

[0014] [5] The above separator film has the above impermeable layer and the above moisture-absorbing layer,

[0015] An optical laminate described in any one of [1] to [4], wherein the first protective layer is a moisture-impermeable layer.

[0016] [6] The above separator film has the above impermeable layer and the above moisture-absorbing layer,

[0017] An optical laminate described in any one of [1] to [4], wherein the above surface protection film includes a moisture-impermeable layer.

[0018] [7] An optical laminate described in any one of [1] to [6], comprising at least one selected from the group consisting of the above-mentioned PVA-based polarizer, the adhesive layer between the first protective layer and the above-mentioned PVA-based polarizer, the adhesive layer between the second protective layer and the above-mentioned PVA-based polarizer, and the above-mentioned adhesive layer α, wherein at least one selected from the group consisting of urea-based compounds, amide compounds and hindered amine-based compounds. Effects of the invention

[0019] According to the present invention, an optical laminate is provided that can suppress yellowing of a PVA-based polarizer in an image display device in a high-temperature environment, even if a member such as an image display cell is attached to one side of a polarizer and a member such as a front plate / touch panel is attached to the other side of the polarizer without performing prior heat treatment of the polarizer. Brief explanation of the drawing

[0020] FIG. 1 is a schematic cross-sectional view of an optical laminate of a first embodiment. FIG. 2 is a schematic cross-sectional view of an optical laminate of a second embodiment. FIG. 3 is a schematic cross-sectional view of an optical laminate of the third embodiment. FIG. 4 is a schematic cross-sectional view of an optical laminate of the fourth embodiment. FIG. 5 is a schematic cross-sectional view of an optical laminate of the fifth embodiment. Specific details for implementing the invention

[0021] An optical laminate according to one embodiment of the present invention comprises a surface protection film, a first protection layer, a PVA-based polarizer, a second protection layer, an adhesive layer, and a separator film in that order. At least one of the surface protection film and the separator film has a moisture-impermeable layer and a moisture-absorbing layer disposed at a position closer to the PVA-based polarizer than to the moisture-impermeable layer.

[0022] Each embodiment of the optical laminate will be described in more detail below with reference to the drawings.

[0023] (First embodiment)

[0024] As illustrated in FIG. 1, the optical laminate (1000) according to the first embodiment comprises a surface protection film (100), a first protection layer (220), a PVA-based polarizer (210), a second protection layer (230), an adhesive layer α (500), and a separator film (600) in this order. In this embodiment, the surface protection film (100) has a moisture-impermeable layer (150) and a moisture-absorbing layer (140) positioned closer to the PVA-based polarizer (210) than to the moisture-impermeable layer (150). Additionally, the first protection layer (220), the PVA-based polarizer (210), and the second protection layer (230) constitute a polarizing plate (200).

[0025] (PVA-based polarizer (210))

[0026] A PVA-based polarizer is a film that selectively transmits direct polarization in a specific direction from natural light. A PVA-based polarizer is a polyvinyl alcohol-based resin film in which a dichroic pigment is oriented. Examples of dichroic pigments include iodine and dichroic dyes.

[0027] The polyvinyl alcohol-based resin constituting the polyvinyl alcohol-based resin film is obtained by saponifying a polyvinyl acetate-based resin. As for the polyvinyl acetate-based resin, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate and other monomers copolymerizable thereto are used. Examples of other monomers copolymerizable to vinyl acetate include, for instance, unsaturated carboxylic acid compounds, olefin compounds, vinyl ether compounds, unsaturated sulfone compounds, and (meth)acrylamide compounds having ammonium groups.

[0028] In addition, in this specification, "(meth)acrylic" means either acrylic or methacrylic, and "(meth)" in (meth)acrylate, etc., has the same meaning.

[0029] The degree of saponification of the polyvinyl alcohol-based resin is typically 85 mol% or more and 100 mol% or less, and preferably 99 mol% or more. The polyvinyl alcohol-based resin may be modified, and polyvinyl formal, polyvinyl acetal, etc. modified with aldehydes may also be used. The average degree of polymerization of the polyvinyl alcohol-based resin is typically 1,000 or more and 10,000 or less, and preferably 1,500 or more and 5,000 or less. The average degree of polymerization of the PVA-based resin can be determined in accordance with JIS K 6726 (1994). If the average degree of polymerization is less than 100, it is difficult to obtain desirable polarization performance, and if it exceeds 10,000, film processability may be reduced.

[0030] A method for manufacturing a PVA-based polarizer having a dichroic pigment oriented on a polyvinyl alcohol-based resin film is not particularly limited, but may include, for example, a dyeing process in which the polyvinyl alcohol-based resin film is dyed with a dichroic pigment such as iodine or a dichroic dye, a crosslinking process in which the polyvinyl alcohol-based resin film after the dyeing process is treated with a crosslinking solution containing a crosslinking agent (e.g., boric acid), and a stretching process in which the polyvinyl alcohol-based resin film is uniaxially stretched.

[0031] The thickness of the PVA-based polarizer is typically 1 to 30 μm, preferably 2 to 25 μm, and more preferably 2 to 20 μm.

[0032] (Urea-based compounds, amide compounds, and hindered amine compounds)

[0033] The PVA-based polarizer may include at least one compound selected from urea-based compounds, amide compounds, and hindered amine-based compounds. Urea-based compounds are urea, urea derivatives, thiourea, and thiourea derivatives.

[0034] (element or element derivative)

[0035] A urea derivative refers to a compound having a molecular structure in which a portion of the urea is substituted by a substituent. As a urea derivative, it is preferable that the compound be one in which at least one of the four hydrogen atoms contained in the urea molecule is substituted by a substituent. In this case, there are no particular restrictions on the substituent, but it is preferable that the substituent be one comprising a carbon atom, a hydrogen atom, and an oxygen atom.

[0036] Specific examples of urea derivatives include monosubstituted ureas such as methyl urea, ethyl urea, propyl urea, butyl urea, isobutyl urea, N-octadecyl urea, 2-hydroxyethyl urea, hydroxy urea, acetyl urea, allyl urea, 2-propynyl urea, cyclohexyl urea, phenyl urea, 3-hydroxyphenyl urea, (4-methoxyphenyl) urea, benzyl urea, benzoyl urea, o-tolyl urea, and p-tolyl urea.

[0037] Examples of disubstituted ureas include 1,1-dimethylurea, 1,3-dimethylurea, 1,1-diethylurea, 1,3-diethylurea, 1,3-bis(hydroxymethyl)urea, 1,3-tert-butylurea, 1,3-dicyclohexylurea, 1,3-diphenylurea, 1,3-bis(4-methoxyphenyl)urea, and 1-acetyl-3-methylurea.

[0038] Examples of tetrasubstituted ureas include tetramethylurea, 1,1,3,3-tetraethylurea, 1,1,3,3-tetrabutylurea, and 1,3-dimethoxy-1,3-dimethylurea.

[0039] (Thiourea or thiourea derivative)

[0040] A thiourea derivative refers to a compound having a molecular structure in which a portion of the thiourea is substituted by a substituent. As a thiourea derivative, it is preferable that at least one of the four hydrogen atoms of the thiourea molecule is substituted by a substituent.

[0041] In this case, there are no particular restrictions on the substituents, but it is preferable that they be substituents containing carbon atoms, hydrogen atoms, and oxygen atoms.

[0042] Specific examples of thiourea derivatives include monosubstituted thioureas such as N-methylthiourea, ethylthiourea, propylthiourea, isopropylthiourea, 1-butylthiourea, cyclohexylthiourea, N-acetylthiourea, N-allylthiourea, (2-methoxyethyl)thiourea, N-phenylthiourea, (4-methoxyphenyl)thiourea, N-(2-methoxyphenyl)thiourea, N-(1-naphthyl)thiourea, (2-pyridyl)thiourea, o-tolylthiourea, and p-tolylthiourea.

[0043] Examples of disubstituted thiourea include 1,1-dimethylthiourea, 1,3-dimethylthiourea, 1,1-diethylthiourea, 1,3-diethylthiourea, 1,3-dibutylthiourea, 1,3-diisopropylthiourea, 1,3-dicyclohexylthiourea, N,N-diphenylthiourea, N,N'-diphenylthiourea, 1,3-di(o-tolyl)thiourea, 1,3-di(p-tolyl)thiourea, 1-benzyl-3-phenylthiourea, 1-methyl-3-phenylthiourea, and N-allyl-N'-(2-hydroxyethyl)thiourea.

[0044] Examples of trisubstituted elements include trimethylthiourea, and examples of tetrasubstituted elements include tetramethylthiourea and 1,1,3,3-tetraethylthiourea.

[0045] Among the above urea-based compounds, urea derivatives or thiourea derivatives are preferred, and urea derivatives are more preferred. Among urea derivatives, monosubstituted urea or disubstituted urea is preferred, and monosubstituted is more preferred. Disubstituted urea includes 1,1-substituted urea and 1,3-substituted urea, but 1,3-substituted urea is more preferred.

[0046] Additionally, in this specification, urea, urea derivatives, thiourea, and thiourea derivatives are referred to as urea-based compounds.

[0047] As a method for incorporating a urea-based compound into a PVA-based polarizer, the method described in Japanese Patent Publication No. 2020-204641 may be applied.

[0048] Examples of amide compounds are as follows.

[0049] (amide compound)

[0050] An example of an amide compound is an amide compound represented by the following formula (1).

[0051]

[0052] In Equation (1), R 1A , R 2A and R 3A Each represents, independently, a hydrogen atom, a hydroxyl group, a C1-5 alkyl group, or a C1-5 alkyl group in which one or more hydrogen atoms are substituted with hydroxyl groups. In terms of further suppressing the decrease in transmittance and polarization degree of the polarizer under high-temperature environments, R 1A , R 2A and R 3A is a hydrogen atom, a hydroxyl group, or a C1- to C5 alkyl group, and is also R 1A , R 2A and R 3A It is preferable that the total number of carbon atoms is 1 to 5, and is a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 3 carbon atoms, and also R 1A , R 2A and R 3A It is more preferable that the total number of carbon atoms is 1 to 3. In addition, from the perspective of further suppressing the decrease in transmittance and polarization degree of the polarizer under high-temperature environments, R 3A It is preferable that is a hydrogen atom, and R 1A α is an alkyl group having 1 to 5 carbon atoms, and R 2A ga is a hydrogen atom or a C1-5 alkyl group, and also R 3A It is more desirable that is a hydrogen atom, and R 1A α is an alkyl group having 1 to 3 carbon atoms, and R 2A ga is a hydrogen atom or a C1-3 alkyl group, and also R 3A It is more desirable that is a hydrogen atom, and R 1A ga is a methyl group or an ethyl group, and R 2Aga is a hydrogen atom, a methyl group, or an ethyl group, and also R 3A It is particularly desirable that it be a hydrogen atom.

[0053] Specific examples of amide compounds include acetamide, propionamide, butyric acid amide, valeric acid amide, caproamide, enantamide, isobutyric acid amide, 2-methylbutyric acid amide, isovaleramide, pivalamide, 2-methylvaleric acid amide, 2-ethylvaleric acid amide, 3-methylvaleric acid amide, 2-ethylbutyric acid amide, 2,2-dimethylbutyric acid amide, glycolamide, lactamide, gluconamide, glycerinamide, 2-hydroxypropanamide, 2-hydroxybutyric acid amide, 3-hydroxybutyric acid amide, γ-hydroxybutyric acid amide, mevalonamide, pantophosphate amide, etc. The amide compounds may be used alone or in combination of two or more types.

[0054] (Hindered amine compounds)

[0055] Hindered amine compounds are secondary or tertiary amines in which an alkyl group is substituted on a carbon adjacent to an amino group to stereoprotect the amino group; for example, compounds having the following structure may be cited. R 1 represents an oxyradical, a hydrogen atom, a hydroxyl group, or an alkyl group, hydroxyalkyl group, hydroxyalkoxy group, or alkoxy group having 1 to 30 carbon atoms, and R 2 to R 5 is independently represented by a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, n represents 0 or 1, and R 6 represents an arbitrary organic group. R 6 Examples of are hydrogen atoms, hydroxyl groups, carboxyl groups, alkyl groups having 1 to 30 carbon atoms, alkoxy groups, acyloxy groups, aryloxy groups, unsubstituted amino groups, and substituted amino groups (e.g., dialkylamino groups).

[0056]

[0057] R2 to R 5 In terms of availability and water solubility, it is preferable that the alkyl group has 1 to 6 carbon atoms, and more preferable that the alkyl group has 1 to 3 carbon atoms.

[0058] An example of a hindered amine compound is the following compound.

[0059]

[0060]

[0061]

[0062]

[0063] (First protective layer (220) and second protective layer (230))

[0064] The first protective layer (220) and the second protective layer (230) each have the function of protecting the surface of the PVA-based polarizer (210). The PVA-based polarizer (210) and the first protective layer (220), and the PVA-based polarizer (210) and the second protective layer (230) may each be directly laminated together. Here, "directly laminated" includes an embodiment in which the first protective layer (220) and the second protective layer (230) are laminated to the PVA-based polarizer (210) by means of self-adhesion, and an embodiment in which they are laminated through an adhesive layer or a pressure-sensitive adhesive layer. The first protective layer (220) and the second protective layer (230) may be surface-treated (e.g., corona treatment, etc.) to improve adhesion to the PVA-based polarizer (210), and may have a thin layer formed thereon, such as a primer layer (also called an easy-adhesion layer).

[0065] As a protective layer, for example, a resin film with excellent transparency, mechanical strength, thermal stability, moisture barrier properties, isotropy, and stretchability may be used. The resin film may be a thermoplastic resin film. Specific examples of such resins include cellulose-based resins such as triacetylcellulose; polyester-based resins such as polyethylene terephthalate and polyethylene naphthalate; polyethersulfone-based resins; polysulfone-based resins; polycarbonate-based resins; polyamide-based resins such as nylon and aromatic polyamides; polyimide-based resins; polyolefin-based resins such as polyethylene, polypropylene, and ethylene-propylene copolymers; cyclic polyolefin-based resins having cyclo-based and norbornene structures (also called norbornene-based resins); (meth)acrylic-based resins such as polymethyl methacrylate; polyarylate-based resins; polystyrene-based resins; polyvinyl alcohol-based resins; and mixtures thereof. Protective films made of such materials are readily available on the market. In addition, thermosetting resins or UV-curing resins such as (meth)acrylic, urethane, (meth)acrylicurethane, epoxy, and silicone types may also be used. In this specification, "(meth)acrylic" means either acrylic or methacrylic.

[0066] The thickness of the protective layer is preferably 0.1 μm to 60 μm, more preferably 0.5 μm to 40 μm, and even more preferably 1 μm to 30 μm.

[0067] The protective layer may contain any suitable additives depending on the purpose. Examples of additives include, for instance, antioxidants such as hindered phenolic, phosphorus-based, or sulfur-based compounds; stabilizers such as light stabilizers, UV absorbers, weather stabilizers, and heat stabilizers; reinforcing materials such as glass fibers or carbon fibers; near-infrared absorbers; flame retardants such as tris(dibromopropyl)phosphate, trialyl phosphate, or antimony oxide; antistatic agents such as anionic, cationic, or nonionic surfactants; coloring agents such as inorganic pigments, organic pigments, or dyes; organic or inorganic fillers; resin modifiers; plasticizers; lubricants; phase difference reducing agents, etc. The types, combinations, and amounts of the contained additives can be appropriately set according to the purpose or desired characteristics.

[0068] In addition, a coating layer (surface treatment layer) may be provided on the outer surface of the protective layer to impart desired surface optical properties or other features. Specific examples of the surface treatment layer include a hard coat layer, an anti-glare layer, an anti-reflective layer, an antistatic layer, and an anti-fouling layer. The method of forming the surface treatment layer is not particularly limited and known methods may be used. The surface treatment layer may be formed on one side of the protective film or on both sides.

[0069] The second protective layer (230) is preferably a moisture-impermeable layer as described later.

[0070] (Adhesive layer bonding the PVA-based polarizer and the protective layer)

[0071] The PVA-based polarizer and each protective layer may be laminated through an adhesive layer.

[0072] As an adhesive, any suitable adhesive composition (hereinafter also simply referred to as "adhesive") can be used. Specifically, as an adhesive, a water-based adhesive, a solvent-based adhesive, an active energy beam curing adhesive, etc., may be used, but a water-based adhesive is preferred, and a water-based adhesive containing a polyvinyl alcohol-based resin and a crosslinking agent is more preferred. When an adhesive layer is provided on both sides of a PVA-based polarizer (210), it may be formed using the same adhesive or different adhesives.

[0073] The thickness of the adhesive applied above can be set to any appropriate value. For example, it is set so that an adhesive layer having a desired thickness is obtained after curing or after heating (drying). The thickness of the adhesive layer is preferably 0.01 μm to 7 μm, more preferably 0.01 μm to 5 μm, even more preferably 0.01 μm to 2 μm, and most preferably 0.01 μm to 1 μm.

[0074] (Water-based adhesive)

[0075] Any suitable water-based adhesive may be used as the water-based adhesive. Among these, a water-based adhesive (PVA-based adhesive) containing a polyvinyl alcohol (PVA)-based resin is preferably used. The water-based adhesive may be a solution obtained by dissolving at least one selected from the group consisting of a PVA-based resin, a urea-based compound, an amide compound, and a hindered amine-based compound in water (e.g., pure water). The average degree of polymerization of the PVA-based resin included in the water-based adhesive is preferably 100 to 5500, more preferably 1000 to 4500, in terms of adhesion. The average degree of saponification is preferably 85 mol% to 100 mol%, more preferably 90 mol% to 100 mol%, in terms of adhesion.

[0076] As for the PVA-based resin included in the above-mentioned water-based adhesive, it is preferable that it contains acetoacetyl groups, because the adhesion between the PVA-based resin layer and the protective film is excellent and the durability is excellent. The acetoacetyl group-containing PVA-based resin is obtained, for example, by reacting a PVA-based resin with diketene by any method. The degree of acetoacetyl group modification of the acetoacetyl group-containing PVA-based resin is typically 0.1 mol% or more, and preferably about 0.1 mol% to 20 mol%.

[0077] The resin concentration of the above-mentioned water-based adhesive is preferably 0.1 mass% to 15 mass%, and more preferably 0.5 mass% to 10 mass%.

[0078] The content of PVA-based resin in the water-based adhesive (the ratio of PVA-based resin to the resin contained in the adhesive) is preferably 80 mass% or more based on the total amount of resin in the water-based adhesive, more preferably 90 mass% or more, and may be 100 mass%.

[0079] (Crosslinking agent, solvent)

[0080] The water-soluble PVA-based adhesive that can be preferably used in the present invention may contain a crosslinking agent as needed in addition to the above-mentioned PVA-based resin. Known crosslinking agents may be used as crosslinking agents. Examples include water-soluble epoxy compounds, dialdehydes, isocyanates, etc.

[0081] In the case where the PVA resin is an acetoacetyl group-containing PVA-based resin, the crosslinking agent is preferably one of glyoxal, glyoxylate, and methylolmelamine, and is preferably one of glyoxal and glyoxylate, and is particularly preferably glyoxal.

[0082] In addition, water-soluble PVA-based adhesives may contain organic solvents. In such cases, alcohols are preferred due to their miscibility with water, and among alcohols, methanol or ethanol is more preferable.

[0083] When the water-based adhesive comprises at least one selected from the group consisting of urea-based compounds, amide compounds, and hindered amine-based compounds, the content of at least one selected from the group consisting of urea-based compounds, amide compounds, and hindered amine-based compounds is preferably 5 to 90 mass% based on the total solid content of the water-based adhesive, more preferably 10 to 80 mass%, and even more preferably 30 to 80 mass%.

[0084] (Active energy beam curing adhesive)

[0085] As an active energy beam curing adhesive, any suitable adhesive that can be cured by irradiation with active energy beams may be used. Examples of active energy beam curing adhesives include ultraviolet curing adhesives and electron beam curing adhesives. Specific examples of curing types of active energy beam curing adhesives include radical curing types, cation curing types, anion curing types, and combinations thereof (e.g., hybrids of radical curing types and cation curing types).

[0086] Examples of the above active energy beam curable adhesives include adhesives containing, for instance, a compound having a radical polymerizable group such as a (meth)acrylate group or a (meth)acrylamide group (e.g., monomer and / or oligomer) as a curing component. Specific examples of the above active energy beam curable adhesive and the curing method thereof are, for instance, described in Japanese Patent Publication No. 2012-144690.

[0087] At least one of the adhesive layer between the first protective layer (220) and the PVA-based polarizer (210) and the adhesive layer between the second protective layer (230) and the PVA-based polarizer (210) may include at least one selected from the group consisting of the aforementioned urea-based compound, amide compound, and hindered amine-based compound. Only one of the pair of adhesive layers may include at least one selected from the group consisting of the urea-based compound, amide compound, and hindered amine-based compound, but it is preferable that both include at least one selected from the group consisting of the urea-based compound, amide compound, and hindered amine-based compound.

[0088] (Adhesive layer α(500))

[0089] As an adhesive composition forming the adhesive layer α (500), any conventionally known adhesive composition with excellent optical transparency can be used without particular limitation, and, for example, an adhesive composition having a base polymer such as an acrylic resin, a urethane resin, a silicone resin, or a polyvinyl ether resin can be used. In addition, an active energy beam curable adhesive composition, a thermosetting adhesive composition, etc. may also be used. Among these, an adhesive composition having an acrylic resin as a base polymer with excellent transparency, adhesive strength, re-peeling properties, weather resistance, and heat resistance is suitable.

[0090] The adhesive composition may further include a crosslinking agent, a silane compound, an antistatic agent, etc.

[0091] [(Matte)Acrylic Resin]

[0092] The (meth)acrylic resin included in the adhesive composition is preferably a polymer (hereinafter also referred to as a "(meth)acrylic acid ester polymer") having a structural unit derived from an alkyl meth)acrylate represented by the following formula (I) as the main component (e.g., containing 50 parts by mass or more per 100 parts by mass of the structural unit of the (meth)acrylic resin).

[0093] In addition, in this specification, the term "(meth)acrylic resin" means either acrylic resin or methacrylic resin, and "(meth)" in (meth)acrylate, etc., has the same meaning.

[0094]

[0095] [In the middle of the meal, R 10 represents a hydrogen atom or a methyl group, and R 20 ...represents an alkyl group having 1 to 20 carbon atoms, and the alkyl group may have a straight-chain, branched, or cyclic structure, and the hydrogen atoms of the alkyl group may be substituted with an alkoxy group having 1 to 10 carbon atoms.

[0096] As for the (meth)acrylic acid ester represented by formula (I), for example, methyl(meth)acrylate, ethyl(meth)acrylate, n-propyl(meth)acrylate, i-propyl(meth)acrylate, n-butyl(meth)acrylate, i-butyl(meth)acrylate, n-pentyl(meth)acrylate, n-hexyl(meth)acrylate, i-hexyl(meth)acrylate, n-heptyl(meth)acrylate, n-octyl(meth)acrylate, i-octyl(meth)acrylate, 2-ethylhexyl(meth)acrylate, n- and i-nonyl(meth)acrylate, n-decyl(meth)acrylate, i-decyl(meth)acrylate, n-dodecyl(meth)acrylate, cyclohexyl(meth)acrylate, Examples include isoboronyl (meth)acrylate, stearyl (meth)acrylate, t-butyl (meth)acrylate, etc. Specific examples of alkoxy group-containing alkyl acrylates include 2-methoxyethyl (meth)acrylate and ethoxymethyl (meth)acrylate. Among these, it is preferable to include n-butyl (meth)acrylate or 2-ethylhexyl (meth)acrylate, and particularly preferable to include n-butyl (meth)acrylate.

[0097] The (meth)acrylic acid ester polymer may include constituent units derived from monomers other than structural unit (I). The structural units derived from other monomers may be one type or two or more types. Other monomers that the (meth)acrylic acid ester polymer may include monomers having polar functional groups, monomers having aromatic groups, and acrylamide-based monomers.

[0098] Examples of monomers having polar functional groups include (meth)acrylates having polar functional groups. Examples of polar functional groups include hydroxyl groups; carboxyl groups; substituted amino groups or unsubstituted amino groups substituted with alkyl groups having 1 to 6 carbon atoms; heterocyclic groups such as epoxy groups. Monomers having polar functional groups may be carboxyl group-containing monomers such as acrylic acid or maleic acid.

[0099] The content of structural units derived from monomers having polar functional groups in the (meth)acrylic acid ester polymer is, with respect to 100 parts by mass of total structural units of the (meth)acrylic acid ester polymer, preferably 10 parts by mass or less, more preferably 0.5 parts by mass or more and 10 parts by mass or less, even more preferably 0.5 parts by mass or more and 5 parts by mass or less, and particularly preferably 1 part by mass or more and 5 parts by mass or less.

[0100] Examples of monomers having aromatic groups include (meth)acrylic acid esters having one (meth)acryloyl group and one or more aromatic rings (e.g., benzene ring, naphthalene ring, etc.) within the molecule, and having a phenyl group, a phenoxyethyl group, or a benzyl group. By including these structural units, the whitening phenomenon of the polarizing plate occurring in high temperature and high humidity environments can be suppressed.

[0101] The content of structural units derived from monomers having aromatic groups in the (meth)acrylic acid ester polymer is preferably 20 parts by mass or less, more preferably 4 parts by mass or more and 20 parts by mass or less, and even more preferably 4 parts by mass or more and 15 parts by mass or less, based on 100 parts by mass of the total structural units of the (meth)acrylic acid ester polymer.

[0102] Examples of acrylamide-based monomers include N-(methoxymethyl)acrylamide, N-(ethoxymethyl)acrylamide, N-(propoxymethyl)acrylamide, N-(butoxymethyl)acrylamide, N-(2-methylpropoxymethyl)acrylamide, etc. By including these structural units, the bleed-out of additives such as antistatic agents described later can be suppressed.

[0103] In addition, structural units derived from monomers other than structural unit (I) may include structural units derived from styrene monomers, structural units derived from vinyl monomers, structural units derived from monomers having multiple (meth)acryloyl groups in the molecule, etc.

[0104] The weight average molecular weight (hereinafter also simply referred to as "Mw") of the (meth)acrylic resin (1) is preferably 500,000 to 2,500,000. If the weight average molecular weight is 500,000 or more, the durability of the adhesive layer can be improved under high temperature and high humidity environments. If the weight average molecular weight is 2,500,000 or less, the operability when applying a coating solution containing the adhesive composition is improved. The molecular weight distribution (Mw / Mn), expressed as the ratio of the weight average molecular weight (Mw) to the number average molecular weight (hereinafter also simply referred to as "Mn"), is typically 2 to 10. In this specification, "weight average molecular weight" and "number average molecular weight" are polystyrene equivalent values ​​measured by gel permeation chromatography (GPC).

[0105] It is preferable that the (meth)acrylic resin, when dissolved in ethyl acetate to form a solution with a concentration of 20 mass%, has a viscosity of 20 Pa·s or less at 25°C, and more preferable that it has a viscosity of 0.1 to 15 Pa·s. If the viscosity of the (meth)acrylic resin at 25°C is within the above range, it contributes to the improvement of durability or reworkability of a polarizing plate including an adhesive layer formed by the resin. The viscosity can be measured by a Brookfield viscometer.

[0106] The glass transition temperature (Tg) of the (meth)acrylic resin is, for example, -60 to 20°C, preferably -50 to 15°C, more preferably -45 to 10°C, and even more preferably -40 to 0°C. In addition, the glass transition temperature can be measured by differential scanning calorimetry (DSC).

[0107] The (meth)acrylic resin may include two or more types of (meth)acrylic acid ester polymers. Examples of such (meth)acrylic acid ester polymers include a relatively low molecular weight (meth)acrylic acid ester polymer having a weight average molecular weight in the range of 50,000 to 300,000, which has a structural unit (I) derived from the above (meth)acrylic acid ester as its main component.

[0108] (Meth)acrylic resins can generally be manufactured by known polymerization methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. In the manufacture of (meth)acrylic resins, polymerization is typically carried out in the presence of a polymerization initiator. The amount of polymerization initiator used is typically 0.001 to 5 parts by mass per 100 parts by mass of the total of all monomers constituting the (meth)acrylic resin. (Meth)acrylic resins can also be manufactured by a method of polymerization using active energy rays such as ultraviolet rays.

[0109] [Crosslinking agent]

[0110] It is preferable that the adhesive composition includes a crosslinking agent. Common crosslinking agents (e.g., isocyanate compounds, epoxy compounds, aziridine compounds, metal chelate compounds, peroxides, etc.) may be used as crosslinking agents, and it is particularly preferable that the isocyanate-based compound be used in relation to the pot life of the adhesive composition, the crosslinking rate, and the durability of the polarizer.

[0111] Isocyanate compounds are compounds having at least two isocyanato groups (-NCO) within the molecule. Specifically, examples include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, etc. In addition, adducts obtained by reacting these isocyanate compounds with polyols such as glycerol or trimethylolpropane, or dimers or trimers of these isocyanate compounds, may also be examples. Two or more isocyanate compounds may be combined.

[0112] The ratio of the crosslinking agent is, for example, 0.01 to 10 parts by mass, preferably 0.05 to 5 parts by mass, and more preferably 0.1 to 1 part by mass, per 100 parts by mass of (meth)acrylic resin.

[0113] [Silan compounds]

[0114] The adhesive composition may further contain a silane compound.

[0115] Examples of silane compounds include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropylethoxydimethylsilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, etc.

[0116] In addition, the silane compound may include an oligomer derived from the silane compound.

[0117] The content of the silane compound in the adhesive composition is typically 0.01 to 10 parts by mass, and preferably 0.05 to 5 parts by mass, per 100 parts by mass of (meth)acrylic resin. If the content of the silane compound is 0.01 parts by mass or more, the adhesion between the adhesive layer and the substrate tends to improve, and if the content is 10 parts by mass or less, the bleed-out of the silane compound from the adhesive layer tends to be suppressed.

[0118] Antistatic agent

[0119] The adhesive composition may further include an antistatic agent. Known antistatic agents may be used, and ionic antistatic agents are suitable. Cationic components constituting the ionic antistatic agent may include organic cations and inorganic cations. Examples of organic cations include pyridinium cations, imidazolium cations, ammonium cations, sulfonium cations, phosphonium cations, etc. Examples of inorganic cations include alkali metal cations such as lithium cations, potassium cations, sodium cations, and cesium cations, and alkaline earth metal cations such as magnesium cations and calcium cations. As for anionic components constituting the ionic antistatic agent, either inorganic anions or organic anions may be used, but anionic components containing fluorine atoms are preferred due to their excellent antistatic performance. As anionic components containing fluorine atoms, hexafluorophosphate anions (PF6) - ), bis(trifluoromethanesulfonyl)imide anion[(CF3SO2)2N - ], bis(fluorosulfonyl)imide anion[(FSO2)2N - You can lift the back.

[0120] An ionic antistatic agent that is solid at room temperature is preferred in that it exhibits excellent long-term stability of the antistatic performance of the adhesive composition.

[0121] The content of the antistatic agent is, for example, 0.01 to 20 parts by mass, preferably 0.1 to 10 parts by mass, and more preferably 1 to 7 parts by mass, per 100 parts by mass of (meth)acrylic resin.

[0122] The adhesive composition may include one or more additives such as a UV absorber, a solvent, a crosslinking catalyst, a tackifier, and a plasticizer. In addition, it is useful to incorporate a UV-curable compound into the adhesive composition and, after forming the adhesive layer, irradiate it with UV light to cure it, thereby making it a harder adhesive layer.

[0123] The adhesive layer α (500) can be formed, for example, by dissolving or dispersing the adhesive composition in a solvent to form a solvent-containing adhesive composition, and then applying this to the surface of a layer to provide the adhesive layer and drying it.

[0124] The thickness of the adhesive layer α (500) is typically 0.1 to 30 μm, preferably 3 to 30 μm, and more preferably 5 to 25 μm.

[0125] The adhesive layer α (500) may include at least one selected from the group consisting of the aforementioned urea-based compounds, amide compounds, and hindered amine-based compounds.

[0126] The peeling force of the adhesive layer α and the second protective layer (230) is greater than the peeling force of the surface protective film (100) and the first protective layer, and the peeling force of the surface protective film (100) and the first protective layer is greater than the peeling force of the adhesive layer α and the separator film (600).

[0127] The peel strength of the adhesive layer α and the separator film (600) may be 0.02 N / 25 mm or greater, or 0.1 N / 25 mm or less. In this specification, the peel strength is based on the "180-degree peel test method" of JIS Z0237:2009 (Test method for adhesive tapes and adhesive sheets).

[0128] The peeling force of the adhesive layer α and the second protective layer (230) may be 0.5 N / 25 mm or more.

[0129] (Surface protection film (100))

[0130] In this embodiment, the surface protection film (100) has, in order from the PVA-based polarizer (210) side, an adhesive layer (110), a substrate layer (120), an adhesive layer (130), a moisture-absorbing layer (140), a moisture-impermeable layer (150), and a substrate layer (160). The surface protection film (100) can protect the surface of the first protection layer (220) side of the polarizer (200), and, if necessary, can be peeled off from the first protection layer (220) for each adhesive layer (110).

[0131] (Recording layer (120 and 160))

[0132] The substrate layers (120 and 160) function as substrates that support the surface protection film (100).

[0133] As for the substrate layer (120 and 160), it may be a thermoplastic resin film, and examples include polyolefin resins such as polyethylene resins and polypropylene resins; cyclic polyolefin resins; polyester resins such as polyethylene terephthalate or polyethylene naphthalate; polycarbonate resins; (meth)acrylic resins, etc. Among these, a polyester resin such as polyethylene terephthalate is preferred. Each substrate layer may have a single-layer structure, but may also have a multilayer structure of two or more layers. The resin film for the protective film may be a film that has undergone stretching treatment such as uniaxial stretching or biaxial stretching.

[0134] The thickness of the substrate layer (160 and 120) may be, for example, 30 to 200 μm, preferably 30 to 150 μm, and more preferably 30 to 120 μm.

[0135] It is not mandatory to have both the substrate layer (120) and the substrate layer (160); for example, having only one of them is sufficient. Additionally, if at least one of the impermeable layer (150) and the moisture-absorbing layer (140) has sufficient strength and can function as a substrate layer, neither the substrate layer (120) nor the substrate layer (160) is required.

[0136] (Adhesive layer (110) and adhesive layer (130))

[0137] The adhesive layer (110) is for fixing the substrate layer (120) to the first protective layer (220). The adhesive layer (130) is for fixing the moisture-absorbing layer (140) and the substrate layer (120). As the adhesive layers (110 and 130), the adhesive layer α (500) exemplified can be used.

[0138] In terms of suitably peeling the surface protection film (100) from the polarizing plate (200), the peeling force of the adhesive layer (110) and the first protection layer (220) may be 0.05 N / 25 mm or more, and 0.2 N / 25 mm or less.

[0139] If the substrate layer (120) is not present, the adhesive layer (130) becomes unnecessary.

[0140] The thickness of the adhesive layer (110, 130) is preferably 5 μm or more, may be 10 μm or more, may be 15 μm or more, and may also be 30 μm or less, may be 25 μm or less, and may be 20 μm or less.

[0141] (Impermeable layer (150))

[0142] The impermeable layer (150) is a layer that sufficiently prevents the penetration of moisture. In this specification, the impermeable layer refers to a layer in which the moisture permeability A measured under conditions of 40°C and 90% relative humidity by the dry-wet sensor method (so-called Lyssy method) in accordance with JIS K7129-1:2019 is 1.5 g / ㎡ / day or less.

[0143] The moisture permeability A of the impermeable layer (150) may be 1.5 g / ㎡ / day or less, 0.3 g / ㎡ / day or less, and less than 0.2 g / ㎡ / day.

[0144] The moisture-impermeable layer (150) has a moisture permeability B of 5.0×10, measured under conditions of 40°C and 90% relative humidity by the differential pressure sensor method (JIS K 7129-5:2016). -4It is acceptable to have less than g / ㎡ / day.

[0145] Examples of layers exhibiting such moisture permeability include cycloolefin polymer films and aluminum layers (e.g., aluminum foil or aluminum deposition films).

[0146] The thickness of the impermeable layer (150) can be appropriately set within a range that satisfies a moisture permeability of 1.5 g / m² / day or less. Specifically, it may be 10 to 100 μm for a cycloolefin polymer film and 5 to 100 μm for an aluminum foil.

[0147] (Absorbent layer (140))

[0148] A hygroscopic layer is a layer capable of sufficiently absorbing water. In this specification, a layer having an absorption amount of 0.3 g / m² or more when stored for 14 days in an environment of 23°C and 55% relative humidity is referred to as a hygroscopic layer. The absorption amount of the hygroscopic layer may be 1.0 g / m² or more, or 3.0 g / m² or more.

[0149] As a material constituting the hygroscopic layer, a composition including a water-adsorbent resin or a hygroscopic agent may be used. As the water-adsorbent resin, polyvinylpyrrolidone-based resins, polyacrylic acid, sodium polyacrylate, polyvinylamine, sodium polyglutamate, polyvinyl alcohol-based resins, and cellulose derivatives may be used. In addition, as the hygroscopic agent, chemical hygroscopic agents such as metal halides, metal oxides, and sulfates, or physical hygroscopic agents such as hydrophilic zeolites or silica gel may be used. The hygroscopic agent may be used alone or in combination.

[0150] As a composition containing a hygroscopic agent, for example, a composition containing a hygroscopic agent and a resin may be used, and the hygroscopic agent may be dispersed within the resin. As a resin for dispersion, for example, a polyolefin resin, a polyester resin, a polyamide resin, or a vinyl polymer may be used.

[0151] Examples of polyolefin resins include polyethylene resins and polypropylene resins.

[0152] Examples of metal oxides include calcium oxide and aluminum oxide. Examples of metal halides include calcium chloride. Examples of sulfates include magnesium sulfate.

[0153] As a hydrophilic zeolite, for example, a type A, type X, or LSX type zeolite can be used.

[0154] In order to ensure good moisture absorption capacity, it is desirable that the content of the absorbent be at least 1 mass% with respect to the total mass of the absorbent layer.

[0155] Method for manufacturing a hygroscopic layer

[0156] The method of producing the moisture-absorbing layer is not particularly limited, and known or conventional methods of production may be applied. For example, it may be performed by wet lamination, dry lamination, solvent-free dry lamination, extrusion lamination, T-die co-extrusion molding, co-extrusion lamination, inflation, or any other method. For example, a moisture-absorbing film can be obtained by melt-kneading 80 parts by mass of polyethylene resin and 20 parts by mass of calcium oxide.

[0157] At least one of the substrate layer (120), substrate layer (160), adhesive layer (110), and adhesive layer (130) of the surface protection film (100) may include an antistatic agent. Additionally, an antistatic layer containing an antistatic agent may be provided on a side opposite to the surface where the adhesive layer (110) in the substrate layer (120) is laminated, or on a side opposite to the surface where the moisture-impermeable layer (150) in the substrate layer (160) is provided.

[0158] Examples of antistatic agents include ionic compounds, ionic polymers, conductive polymers, conductive microparticles, surfactants, hydrolyzable organosilicon compounds, and their condensates. Ionic compounds are compounds having an inorganic cation or an organic cation and an inorganic anion or an organic anion. Examples of ionic polymers include polymers containing ammonium salts or sodium sulfonate. Examples of conductive polymers include polyacetylene, polyphenylene, polystyrene sulfonic acid, etc. Two or more types of ionic compounds of the above antistatic agents may be used.

[0159] (Separate film (600))

[0160] The separator film (600) has a substrate layer (610). The separator film (600) can protect the surface of the adhesive layer α (500) and, if necessary, can be peeled off from the adhesive layer α (500).

[0161] (Recording layer (610))

[0162] The substrate layer (610) is a layer that supports the separator film (600). As the substrate layer (610), the substrate layer (120 and 160) exemplified may be used. The thickness of the substrate layer (610) may be, for example, 30 to 200 μm, preferably 30 to 150 μm, and more preferably 30 to 120 μm. The surface of the substrate layer (610) that contacts the adhesive layer α may be subjected to a known release treatment.

[0163] The substrate layer (610) of the separator film (600) may include an antistatic agent. Additionally, an antistatic layer containing an antistatic agent may be provided on the side opposite to the adhesive layer α (500) in the substrate layer (610).

[0164] Examples of antistatic agents include ionic compounds, ionic polymers, conductive polymers, conductive microparticles, surfactants, hydrolyzable organosilicon compounds, and their condensates. Ionic compounds are compounds having an inorganic cation or an organic cation and an inorganic anion or an organic anion. Examples of ionic polymers include polymers containing ammonium salts or sodium sulfonate. Examples of conductive polymers include polyacetylene, polyphenylene, polystyrene sulfonic acid, etc. Two or more types of ionic compounds of the above antistatic agents may be used.

[0165] It is preferable that the optical laminate comprises at least one selected from the group consisting of a PVA-based polarizer (210), an adhesive layer (not shown) between a first protective layer (220) and a PVA-based polarizer (210), an adhesive layer (not shown) between a second protective layer and a PVA-based polarizer (not shown), and an adhesive layer α (500), and at least one selected from the group consisting of a urea-based compound, an amide compound, and a hindered amine-based compound. A plurality of these may comprise at least one selected from the group consisting of a urea-based compound, an amide compound, and a hindered amine-based compound. The urea-based compound, the amide compound, and the hindered amine-based compound are as described in the section on the PVA-based polarizer.

[0166] When the optical laminate comprises at least one selected from the group consisting of urea-based compounds, amide compounds, and hindered amine-based compounds, the content of at least one selected from the group consisting of urea-based compounds, amide compounds, and hindered amine-based compounds is preferably 0.001 to 0.2 mass% based on the solid content of the optical laminate, more preferably 0.003 to 0.2 mass%, and even more preferably 0.007 to 0.2 mass%.

[0167] (Second embodiment)

[0168] Next, with reference to FIG. 2, an optical laminate according to a second embodiment will be described. Hereinafter, redundant descriptions will be omitted, and only the differences will be explained.

[0169] The difference between this embodiment and the first embodiment is that the separator film (600) has an adhesive layer (620), a moisture-impermeable layer (640), and a substrate layer (650) in order from the PVA-based polarizer side, on the side opposite to the adhesive layer α (500) of the substrate layer (610). That is, the second embodiment is in the form that the surface protection film (100) has a moisture-impermeable layer and a moisture-absorbing layer, and the separator film (600) has a moisture-impermeable layer. In addition, the first protection layer (220) or the second protection layer (230) may be a moisture-impermeable layer or not a moisture-impermeable layer.

[0170] The adhesive layer (620) is the same as the adhesive layer (130) described above.

[0171] The moisture-impermeable layer (640) is the same as the moisture-impermeable layer (150) described above.

[0172] The substrate layer (650) is identical to the substrate layer (160) described above.

[0173] Additionally, the substrate layer (650) is optional. Also, if the moisture-permeable layer (640) or the substrate layer (650) has sufficient strength, the substrate layer (610) is not required, and in this case, the adhesive layer (620) becomes unnecessary.

[0174] (Third embodiment)

[0175] Next, with reference to FIG. 3, an optical laminate according to a third embodiment will be described.

[0176] The difference between this embodiment and the second embodiment is that the separator film (600) has a moisture-absorbing layer (630) between the adhesive layer (620) and the moisture-impermeable layer (640). The moisture-absorbing layer (630) is positioned closer to the PVA-based polarizer (210) than the moisture-impermeable layer (640). The moisture-absorbing layer (630) is identical to the moisture-absorbing layer (140) described above. That is, the third embodiment is a form in which both the surface protection film (100) and the separator film (600) have a moisture-impermeable layer and a moisture-absorbing layer.

[0177] (Fourth embodiment)

[0178] Next, with reference to FIG. 4, an optical laminate according to a fourth embodiment will be described.

[0179] The difference between the optical laminate (1000) according to the fourth embodiment and the first embodiment is that the surface protection film (100) does not have an adhesive layer (130), a moisture-absorbing layer (140), a moisture-impermeable layer (150), and a substrate layer (160), and the separator film (600) has an adhesive layer (620), a moisture-absorbing layer (630), a moisture-impermeable layer (640), and a substrate layer (650) in order from the PVA-based polarizer (210) side, opposite to the PVA-based polarizer (210) of the substrate layer (610). That is, the fourth embodiment is a form in which the surface protection film (100) does not have a moisture-absorbing layer and a moisture-impermeable layer, and the separator film (600) has a moisture-impermeable layer and a moisture-absorbing layer.

[0180] The adhesive layer (620) is the same as the adhesive layer (130) of the first embodiment, the moisture-absorbing layer (630) is the same as the moisture-absorbing layer (140) of the first embodiment, the moisture-impermeable layer (640) is the same as the moisture-impermeable layer (150) of the first embodiment, and the substrate layer (650) is the same as the substrate layer (160) of the first embodiment.

[0181] It is not essential to have both the substrate layer (610) and the substrate layer (650), for example, having only one of them is sufficient, and also, if at least one of the moisture-impermeable layer (640) and the moisture-absorbing layer (630) has sufficient strength and can function as a substrate layer, it is not necessary to have both the substrate layer (610) and the substrate layer (650).

[0182] If the substrate layer (610) is not present, the adhesive layer (620) becomes unnecessary.

[0183] In this embodiment, the first protective layer (220) is preferably a moisture-impermeable layer.

[0184] (Fifth embodiment)

[0185] Next, with reference to FIG. 5, an optical laminate according to the fifth embodiment will be described.

[0186] The difference between the optical laminate (1000) according to the fifth embodiment and the fourth embodiment is that the surface protection film (100) has an adhesive layer (130), a moisture-impermeable layer (150), and a substrate layer (160) in order from the PVA-based polarizer (210) side, opposite to the PVA-based polarizer (210) of the substrate layer (120). That is, the fifth embodiment is in the form that the surface protection film (100) has a moisture-impermeable layer, and the separator film (600) has a moisture-impermeable layer and a moisture-absorbing layer.

[0187] Additionally, it is not essential to have both the substrate layer (120) and the substrate layer (160), for example, having only one of them is sufficient, and also, if the moisture-permeable layer (150) has sufficient strength and can function as a substrate layer, it is not necessary to have both the substrate layer (120) and the substrate layer (160).

[0188] If the substrate layer (120) is not present, the adhesive layer (130) becomes unnecessary.

[0189] (How to use optical laminates)

[0190] Next, an example of a method for manufacturing an image display device using an optical laminate (1000) is described.

[0191] First, a separator film (600) is peeled off from the optical laminate (1000), and the laminate of the surface protection film (100) and the polarizer (200) is bonded to an image display cell through an adhesive layer α.

[0192] Next, the surface protection film (100) is peeled off from the polarizing plate (200). Next, a front plate or touch panel is attached to the peeled surface of the polarizing plate through an adhesive layer, etc.

[0193] Accordingly, an image display device with a layered structure, such as an image display cell, a polarizer, a front panel, or a touch panel, can be obtained. Furthermore, heat treatment of the polarizer is not required during the period from attaching one side of the polarizer to the image display cell until attaching the front panel or touch panel to the other side of the polarizer.

[0194] (Effective effects)

[0195] According to the optical laminate of the present embodiment, yellowing of a PVA-based polarizer in a high-temperature environment in an image display device having a layer structure, such as an image display cell / polarizer / front plate or touch panel, can be suppressed. Although the reason is not clear, the following mechanism of action can be conceived.

[0196] In the above-described embodiment, at least one of the surface protection film (100) and the separator film (600) has a combination of a moisture-impermeable layer (150) and a moisture-absorbing layer (140) positioned closer to the PVA-based polarizer (210) than the moisture-impermeable layer (150), or a combination of a moisture-impermeable layer (640) and a moisture-absorbing layer (630) positioned closer to the PVA-based polarizer (210) than the moisture-impermeable layer (640). Accordingly, moisture within the PVA-based polarizer can be absorbed by the moisture-absorbing layer while suppressing the movement of moisture from the outside of the optical laminate to the moisture-absorbing layer by the moisture-impermeable layer, and the amount of moisture within the PVA-based polarizer can be reduced. Therefore, it is believed that an image display device having an image display panel, a polarizer, and a front panel / touch panel laminated together can be obtained with the moisture within the PVA-based polarizer reduced. For this reason, the yellowing of the PVA-based polarizer in this image display device is reduced even when exposed to a high-temperature environment. Furthermore, it is believed that if moisture is contained in the PVA-based polarizer, the decomposition of the iodine complex under high-temperature conditions is accelerated, and polyenification occurs with free iodine acting as a catalyst, causing yellowing.

[0197] In cases where only one side of the surface protection film (100) and the separator film (600) has a moisture-impermeable layer and a moisture-absorbing layer, or where the second protection layer (230) of the first embodiment (Fig. 1) is a moisture-impermeable layer, or where the first protection layer (220) of the fourth embodiment (Fig. 4) is a moisture-impermeable layer, if the protection layer on the side opposite to one side of the surface protection film (100) and the separator film (600) is a moisture-impermeable layer with the PVA-based polarizer (210) in between, the supply of moisture from the opposite side is also suppressed, and the effect is even higher.

[0198] In addition, when only one side of the surface protection film (100) and the separator film (600) has a moisture-impermeable layer and a moisture-absorbing layer, if the other side of the surface protection film (100) and the separator film (600) has a moisture-impermeable layer, as in the second embodiment (Fig. 2) or the fifth embodiment (Fig. 5), the effect is even higher.

[0199] In addition, as shown in the third embodiment (Fig. 3), if both the surface protection film (100) and the separator film (600) each have an impermeable layer and a moisture-absorbing layer, the effect is even higher.

[0200] In addition, if at least one selected from the group consisting of a PVA-based polarizer, an adhesive layer between the first protective layer and the PVA-based polarizer, an adhesive layer between the second protective layer and the PVA-based polarizer, and an adhesive layer α includes at least one selected from the group consisting of a urea-based compound, an amide compound, and a hindered amine-based compound, the effect is further enhanced.

[0201] Examples

[0202] (Preparation of each film)

[0203] The following film was prepared.

[0204] · Laminated film A: A laminated film comprising a PET film (PET1), an impermeable layer (aluminum foil (AL1)), and a moisture-absorbing layer (obtained by cutting the moisture-absorbing group (R) (product name TO-A2) obtained from Maruto Sangyo Co., Ltd.)

[0205] The water vapor permeability A of the aluminum foil (AL1) as an impermeable layer is less than 0.2 g / ㎡ / day, and the water vapor permeability B is 5.0×10 -4 It was less than g / ㎡ / day.

[0206] The absorption capacity of the hygroscopic layer was 6.62 g / m².

[0207] ·Laminated film B: A laminated film comprising PET film (PET2) / adhesive layer A.

[0208] The peel strength of the adhesive layer A and the TAC of the polarizer was 0.06 N / 25 mm.

[0209] The moisture permeability A of the PET2 film was 15 g / m² / day.

[0210] ·PET3: A PET film with one side treated for release.

[0211] ·AL2: Aluminum foil (moisture permeability A is less than 0.2 g / ㎡ / day, moisture permeability B is 5.0×10⁻⁶ -4 It was less than g / ㎡ / day.

[0212] · COP: Cycloolefin resin film (thickness 51 μm, moisture permeability A was 1.5 g / m² / day.)

[0213] ·TAC: Triacetylcellulose film (thickness 40 µm)

[0214] · Adhesive Layer B: Peel force with polarizer TAC 15 N / 25 mm

[0215] Peel strength with PET3 0.04 N / 25 mm

[0216] · Adhesive layer C: Acrylic adhesive

[0217] Method for manufacturing water-based adhesives A to G

[0218] Z-200 (acetoacetyl-modified PVA manufactured by Mitsubishi Chemical Corporation) was dissolved in pure water to obtain a 5.7 wt% aqueous solution. Pure water, the above 5.7 wt% Z-200 aqueous solution, a 40 wt% glyoxal solution (manufactured by Fujifilm Wako Junyaku Co., Ltd.), and the additives shown in Table 1 were mixed such that the weight ratio of water / Z-200 (solid content) / glyoxal (solid content) / additives in the adhesive was 100 / 3.0 / 0.15 / X to obtain water-based adhesives A to G. Here, the amount of additives was adjusted so that the mass ratio X was the value shown in Table 1 below.

[0219] For the obtained water-based adhesives A to G, the concentration of additives per 1 kg of adhesive was calculated using the following formula.

[0220] Additive concentration (mol / kg) = Amount of additive added (kg) / Molecular weight of additive (kg / mol) × 1 / Amount of adhesive preparation (kg)

[0221]

[0222] Method for manufacturing a PVA-based polarizer

[0223] A long polyvinyl alcohol film with a thickness of 30 μm (VF-PE#3000 manufactured by Kuraray Co., Ltd.) was continuously conveyed and immersed in a swelling bath consisting of pure water at 20°C for a residence time of 31 seconds (swelling process). Afterwards, the film withdrawn from the swelling bath was immersed in a dyeing bath at 30°C containing iodine with a potassium iodide / water ratio of 2 / 100 (weight ratio) for a residence time of 122 seconds (dyeing process). Subsequently, the film withdrawn from the dyeing bath was immersed in a crosslinking bath at 56°C containing potassium iodide / boric acid / water in a weight ratio of 12 / 4.1 / 100 (weight ratio) for a residence time of 70 seconds, and then immersed in a crosslinking bath at 40°C containing potassium iodide / boric acid / water in a weight ratio of 9 / 2.9 / 100 (crosslinking process).

[0224] In the dyeing and crosslinking processes, axial stretching in the MD direction was performed by roller-to-roll stretching in the bath. The total stretching ratio based on the fabric film was set to 5.5 times. Next, the film withdrawn from the crosslinking bath was immersed in a washing bath consisting of pure water at 5°C for a residence time of 3 seconds (washing process), then introduced into a drying oven at 80°C for a residence time of 190 seconds and dried (drying process) to obtain a polarizer. The thickness of the polarizer obtained in this example was 12 μm.

[0225] Fabrication of polarizing plates A to G

[0226] Using a roll-type laminator, triacetylcellulose films with a thickness of 40 μm that have undergone saponification treatment were bonded to both sides of a PVA-based polarizer using a water-based adhesive as described in Table 1, and the resulting laminate was dried at 80°C for 3 minutes to obtain polarizers A to G. The composition of the polarizers is TAC / PVA-based polarizer / TAC.

[0227] Production of surface protection film A

[0228] · Surface protection film A was obtained by laminating the moisture-absorbing layer side of laminated film A through the adhesive layer C onto the PET2 side of laminated film B.

[0229] The composition of surface protection film A is laminated film A (PET1 / impermeable layer (AL1) / hygroscopic layer) / adhesive layer C / laminated film B (PET2 / adhesive layer A).

[0230] Production of surface protection film B

[0231] · A surface protection film B was obtained by laminating COP through an adhesive layer C onto the PET2 surface of laminated film B.

[0232] The composition of surface protection film B is COP / adhesive layer C / laminated film B (PET2 / adhesive layer A).

[0233] Production of surface protection film C

[0234] · A surface protection film C was obtained by laminating AL2 through an adhesive layer C onto the PET2 surface of laminated film B.

[0235] The composition of surface protection film C is AL2 / adhesive layer C / laminated film B (PET2 / adhesive layer A).

[0236] Production of Separate Film A

[0237] Separate film A was obtained by laminating COP through adhesive layer C on the side opposite to the release treatment surface of PET3.

[0238] The composition of separator film A is PET3 / adhesive layer C / COP.

[0239] Production of Separate Film B

[0240] Separate film B was obtained by laminating AL2 through adhesive layer C on the side opposite to the release treatment surface of PET3.

[0241] The composition of separator film B is PET3 / adhesive layer C / AL2.

[0242] Production of Separate Film C

[0243] Separate film C was obtained by laminating the moisture-absorbing layer side of laminated film A through the adhesive layer C on the side opposite to the release treatment surface of PET3.

[0244] The composition of separator film C is PET3 / adhesive layer C / laminated film A (hygroscopic layer / impermeable layer (AL1) / PET1).

[0245] Manufacturing of an optical laminate (polarizing plate equipped with a moisture-absorbing layer)

[0246] <Example 1>

[0247] Corona treatment was performed on the TAC surface of one side of polarizer A, and adhesive B and separator film A (PET3 / adhesive layer C / COP) were bonded to the corona-treated surface in this order using a roll laminator.

[0248] Next, a surface protection film A was bonded to the outer side of the TAC on the other side of polarizer A using a roll laminator to obtain an optical laminate (polarizer equipped with a moisture-absorbing layer). The optical laminate was stored for 14 days under humidity control at 23°C and 55% relative humidity.

[0249] The composition of the optical laminate is surface protection film A (PET1 / impermeable layer (AL1) / absorbent layer / adhesive C / PET2 / adhesive A) / polarizer A (TAC / polarizer / TAC) / adhesive layer B / separator film A (PET3 / adhesive layer C / COP).

[0250] <Examples 2–15, Comparative Examples 1–2>

[0251] An optical laminate was obtained in the same manner as in Example 1, except that the separator film, surface protection film, and polarizer were changed to the separator film and surface protection film listed in Table 2. Separator films A to C were bonded such that PET3 was on the polarizer side, and the surface protection film was bonded such that adhesive layer A was on the polarizer side. The optical laminates of Examples 1 and 2 are the second embodiment in this specification, the optical laminates of Examples 3 to 8 are the fifth embodiment, and the laminates of Examples 9 to 15 are the third embodiment.

[0252] In addition, in Comparative Examples 1 and 2, laminated film B was used as the surface protection film, and PET3 was used as the separator film.

[0253] Preparation of samples for durability evaluation <Examples 1 to 15 and Comparative Example 1>

[0254] The obtained optical laminate (polarizer equipped with a hygroscopic layer) was cut to a length of 30 mm in the MD direction (direction of the polarizer's absorption axis) × 30 mm in the TD direction (direction orthogonal to the polarizer's absorption axis), the separator film was peeled off, and adhesive layer B was bonded to the center of an alkali-free glass measuring 40 mm × 40 mm × 0.7 mm in thickness. The laminate configuration at this time was surface protection film / polarizer / adhesive layer B / alkali-free glass. After leaving this laminate for 7 days under controlled humidity of 23°C and 55% relative humidity, the surface protection film was peeled off, and a cover glass measuring 30 mm × 30 mm × 0.15 mm in thickness was bonded to the surface of the polarizer using an acrylic adhesive with a thickness of 25 μm to obtain a sample for durability evaluation.

[0255] The composition of the durability evaluation sample is cover glass / adhesive / polarizer (TAC / polarizer / TAC) / adhesive layer B / alkali-free glass.

[0256] Preparation of a sample for durability evaluation <Comparative Example 2>

[0257] The obtained optical laminate (polarizer equipped with a hygroscopic layer) was cut to a length of 30 mm in the MD direction (direction of the polarizer's absorption axis) × 30 mm in the TD direction (direction orthogonal to the polarizer's absorption axis), the separator film was peeled off, and adhesive layer B was bonded to the center of an alkali-free glass measuring 40 mm × 40 mm × 0.7 mm in thickness. The laminate configuration at this time was surface protection film / polarizer / adhesive layer B / alkali-free glass. This laminate was heated in an oven at 95°C for 3 hours and stored for 24 hours under controlled humidity of 23°C and 55% relative humidity. Afterward, the surface protection film was peeled off, and a cover glass measuring 30 mm × 30 mm × 0.15 mm in thickness was bonded to the surface of the polarizer using an acrylic adhesive with a thickness of 25 μm to obtain a sample for durability evaluation.

[0258] The composition of the durability evaluation sample is cover glass / adhesive / polarizer (TAC / polarizer / TAC) / adhesive layer B / alkali-free glass.

[0259] (Water vapor transmission measurement)

[0260] (Measurement of water vapor transmission A (Lyssy method))

[0261] · Detection method: Humidity sensor method (compliant with JIS K7129-1:2019)

[0262] · Measuring device: Lyssy L80 series water vapor permeability

[0263] · Measurement conditions: 40℃, relative humidity 90%

[0264] · Measured area: 5.0×10 -3 ㎡

[0265] · Lower measurement limit: 0.2 g / ㎡ / day

[0266] ·method:

[0267] (1) A sample was inserted and fixed between the upper chamber (saturated water vapor) and the lower chamber, to which a humidity sensor was attached.

[0268] (2) The upper chamber was dried to a predetermined level (lower humidity limit).

[0269] (3) The upper chamber was humidified by the water vapor permeation of the sample, and the time taken for the humidity of the upper chamber to change from 9.9% to 10.1% was measured, and the transmittance A was calculated from the following formula.

[0270] WVTR sample (g / ㎡ / day)=WVTR std .×T std . / T sample

[0271] WVTR std .: Water vapor permeability of standard sample (g / m² / day)

[0272] T std .: Time for humidity in a standard sample to change from 9.9% to 10.1%

[0273] T sample : Time for humidity in the test sample to change from 9.9% to 10.1%

[0274] (Measurement of water vapor permeability B (Delta Palm))

[0275] · Detection method: Differential pressure sensor method (compliant with JIS K 7129-5:2016)

[0276] · Model: Standard 1-Chamber Manual DP-ST1 CM

[0277] · Measurement conditions: 40℃, relative humidity 90%

[0278] ·method:

[0279] (1) A sample was inserted and fixed between the upper part, to which a steam supply tank was attached, and the lower part, to which a pressure sensor was attached.

[0280] (2) The constant temperature bath was set to 40℃, and vacuum drying was performed in both the upper and lower chambers.

[0281] (3) The upper room was sealed and water vapor with a relative humidity of 40°C and 90% was introduced from the supply side, and the WVTR was calculated from the pressure change over time in the room.

[0282] · Lower measurement limit: 5.0×10 -4 g / ㎡ / day

[0283] (Regulation of absorption capacity of the hygroscopic layer)

[0284] The absorption amount of the hygroscopic layer was calculated using the following method.

[0285] The hygroscopic layer cut to 100×100 mm was vacuum dried at 23°C for 8 hours, and the initial weight was measured. Next, the weight was measured after storing for 2 weeks under 23°C relative humidity of 55%, and the amount of absorption was calculated from the following formula.

[0286] Absorption amount [g / ㎡] = (Weight after storage at 23℃ and 55% relative humidity - Initial weight) × 100

[0287] (Measurement of absorption amount of the hygroscopic layer within laminated film A (hygroscopic group (R))

[0288] The hygroscopic group (R) (product name TO-A2) was cut to a size of 100 mm × 100 mm and vacuum dried at 23°C for 8 hours, and the weight (initial weight) was measured. Next, this film was stored for 2 weeks under an environment of 23°C and 55% relative humidity, and the weight (weight after storage) was measured. The absorption amount of the hygroscopic group (R) was calculated from the following formula.

[0289] Absorption capacity [g / ㎡] = (Weight after storage - Initial weight) × 100

[0290] The absorption amount of the absorption layer of the absorption group (R) was calculated by subtracting the absorption amount of each individual of the PET film (PET1) and the impermeable layer (AL1), which are layers other than the absorption layer within the absorption group (R), from the absorption amount of the obtained absorption group (R) in the same way.

[0291] (Measurement of peel strength)

[0292] · Peeling force of the surface protection film (adhesive layer A) and the TAC of the polarizer

[0293] A laminate was prepared comprising laminate film B (PET film (PET2) / adhesive layer A) / polarizing plate A / adhesive layer (thickness 25 μm). This laminate was cut to a size of 25 mm × 120 mm, and after bonding the adhesive layer to glass, autoclave treatment was performed at a temperature of 50°C and a pressure of 0.49 MPa to obtain a test specimen for evaluating peel strength.

[0294] After storing the test specimen for peel strength evaluation at a temperature of 23°C and a relative humidity of 60% for 24 hours, the PET film and adhesive layer A were peeled from the TAC of polarizer A using an autograph (manufactured by Shimadzu Seisakusho Inc., product name “AGS-X (50N)”) at a peeling angle of 180° and a peeling speed of 300 mm / min, and the peel strength of the surface protection film (adhesive layer A) and the polarizer was obtained by taking the average of the test strength at the time of peeling in the peeling section.

[0295] · Peeling force of adhesive layer α (adhesive layer B) and the TAC of the polarizer

[0296] Except for preparing a laminate comprising a PET film (PET3) / adhesive layer B / polarizing plate A / adhesive layer (thickness 25 μm), the peel strength of the adhesive layer A and the polarizing plate TAC is made the same, and the PET film and adhesive layer B are peeled from the TAC of polarizing plate A to obtain the peel strength of the adhesive layer α (adhesive layer B) and the polarizing plate.

[0297] · Peel strength of adhesive layer α (adhesive layer B) and separator film (PET3)

[0298] A PET film (PET3) with dimensions of 25 mm × 120 mm was prepared. After bonding the PET3 to glass through adhesive layer B, the film was autoclaved at a temperature of 50°C and a pressure of 0.49 MPa to obtain a test specimen for evaluating peel strength. In this test specimen, the release treatment surface of the PET3 was positioned so that it faced the adhesive layer B.

[0299] After storing the test specimen for evaluating peel strength at a temperature of 23°C and a relative humidity of 60% for 24 hours, the PET film was peeled from adhesive layer B using an autograph (manufactured by Shimadzu Seisakusho Inc., product name “AGS-X (50N)”) at a peeling angle of 180° and a peeling speed of 300 mm / min, and the peel strength of adhesive layer α (adhesive layer B) and the separator film was obtained by taking the average of the test strength at the time of peeling in the peeling section.

[0300] As a result of the measurement, in the example, the peeling force when peeling the surface protection film from the polarizer was greater than the peeling force when peeling the separator film from the adhesive layer. In addition, the peeling force when peeling the surface protection film from the polarizer was smaller than the peeling force when peeling the polarizer from the adhesive layer α.

[0301] (Initial measurement of Ty, Py, and individual b values)

[0302] For the durability evaluation samples obtained in each example and each comparative example, MD transmittance and TD transmittance in the wavelength range of 380 to 780 nm were measured using an integrating sphere spectrophotometer (manufactured by Nihon Bunko Co., Ltd., product name: V7100). Subsequently, the single transmittance and polarization degree at each wavelength were given by the following formula:

[0303] Group transmittance (%) = (MD transmittance + TD transmittance) / 2

[0304] Polarization (%) = {(MD transmittance - TD transmittance) / (MD transmittance + TD transmittance)} × 100

[0305] It was calculated based on.

[0306] Here, MD transmittance refers to the transmittance when the direction of polarization from the Glen Thomson prism is parallel to the transmission axis of the durability evaluation sample. Furthermore, TD transmittance refers to the transmittance when the direction of polarization from the Glen Thomson prism is orthogonal to the transmission axis of the durability evaluation sample. Regarding the obtained single-element transmittance and degree of polarization, JIS Z8701:1999 “Methods of Color Representation - XYZ Color System and X 10 Y 10 Z 10 Luminous sensitivity correction was performed using a 2-degree field of view (C light source) of the "color system" to obtain the luminous sensitivity correction single transmittance (Ty), luminous sensitivity correction polarization degree (Py), and single b value. These were set as the initial Ty, Py, and single b. The results are shown in Table 2.

[0307] (Measurement of Ty and Py after high-temperature endurance test)

[0308] A high-temperature endurance test was performed by storing the endurance evaluation sample in a heated environment at 105°C for 500 hours. For the endurance evaluation sample after the high-temperature endurance test, the single transmittance and polarization degree were measured using the same method as above to determine Ty and Py. Based on the obtained values ​​of Ty and Py after the high-temperature endurance test, the effect of suppressing the decrease in transmittance and polarization degree under high-temperature environments was evaluated according to the following criteria. The results are shown in Table 2.

[0309] In addition, yellowing was determined based on the following criteria.

[0310] A: Ty>36%

[0311] B: 36%≥Ty>28%

[0312] C: 28%≥Ty>15%

[0313] D: 15%≥Ty>5%

[0314] E: Ty≤5%

[0315]

[0316] Explanation of the symbols

[0317] 100… surface protection film, 140, 630… moisture-absorbing layer, 150, 640… moisture-impermeable layer, 200… polarizer, 210… PVA-based polarizer, 220… first protective layer, 230… second protective layer, 500… adhesive layer α, 600… separator film, 1000… optical laminate.

Claims

Claim 1 An optical laminate comprising, in this order, a surface protection film, a first protection layer, a PVA-based polarizer, a second protection layer, an adhesive layer α, and a separator film, wherein at least one of the surface protection film and the separator film has a moisture-impermeable layer and a moisture-absorbing layer disposed at a position closer to the PVA-based polarizer than to the moisture-impermeable layer. Claim 2 An optical laminate according to claim 1, wherein the surface protection film has the moisture-impermeable layer and the moisture-absorbing layer, and the second protection layer is the moisture-impermeable layer. Claim 3 An optical laminate according to claim 1, wherein the surface protection film has a moisture-impermeable layer and a moisture-absorbing layer, and the separator film has a moisture-impermeable layer. Claim 4 In paragraph 3, the optical laminate further comprises a moisture-absorbing layer positioned closer to the PVA-based polarizer than to the moisture-impermeable layer, wherein the separator film is further provided with the separator film. Claim 5 An optical laminate according to claim 1, wherein the separator film has the moisture-impermeable layer and the moisture-absorbing layer, and the first protective layer is the moisture-impermeable layer. Claim 6 An optical laminate according to claim 1, wherein the separator film has the moisture-impermeable layer and the moisture-absorbing layer, and the surface protection film includes the moisture-impermeable layer. Claim 7 An optical laminate according to any one of claims 1 to 6, wherein at least one selected from the group consisting of the PVA-based polarizer, the adhesive layer between the first protective layer and the PVA-based polarizer, the adhesive layer between the second protective layer and the PVA-based polarizer, and the adhesive layer α comprises at least one selected from the group consisting of a urea-based compound, an amide compound, and a hindered amine-based compound.